Incentives for Helping on the Job: Theory and Evidence - Drago, Robert; Garvey, Gerald T. (Journal of Labor Economics, 1998)
Recent advances in incentive theory stress the multidimensional nature of agent effort and specifically cases where workers affect one anothers' performance through “helping” efforts. This article models helping efforts as determined by the compensation package and task allocation. The model is tested with Australian evidence on reported helping efforts within work groups. The evidence consistently supports the hypothesis that helping efforts are reduced, while individual efforts are increased, when promotion incentives are strong. Piece rates and profit‐sharing appear to have little effect on helping efforts, while task variety and helping efforts are positively correlated.